2000
DOI: 10.1029/eo081i047p00561-01
|View full text |Cite
|
Sign up to set email alerts
|

Are ocean wave heights increasing in the eastern North Pacific?

Abstract: Erosion, caused in large part by unusually severe storms, has damaged beaches and property in recent years along the Pacific coast of the United States. In the Pacific Northwest (Oregon and Washington), four storms were experienced during the 1998–1999 La Niña winter that produced wave heights which exceeded what had been projected as the 100‐year extreme event. This occurrence raises questions about the effects of climate controls— such as El Niños and La Ni˜nas—on wave conditions in the North Pacific, and wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
93
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(110 citation statements)
references
References 8 publications
13
93
3
Order By: Relevance
“…Qualitatively similar conclusions can be drawn from the comparison with the analysis of Sterl and Caires (2005), who presented February trends in SWH in the same dataset. Our trends in the northeast Pacific are in a qualitative agreement with Allan and Komar (2000) and Gower (2002) estimates for the period from the late 1970s to the late 1990s derived from the in situ buoy data. Quantitative comparison shows that our estimates are somewhat weaker than those reported by buoys that can be explained by the spatial averaging in a gridded product.…”
Section: Secular Changes In Wind Wave Heightssupporting
confidence: 76%
See 1 more Smart Citation
“…Qualitatively similar conclusions can be drawn from the comparison with the analysis of Sterl and Caires (2005), who presented February trends in SWH in the same dataset. Our trends in the northeast Pacific are in a qualitative agreement with Allan and Komar (2000) and Gower (2002) estimates for the period from the late 1970s to the late 1990s derived from the in situ buoy data. Quantitative comparison shows that our estimates are somewhat weaker than those reported by buoys that can be explained by the spatial averaging in a gridded product.…”
Section: Secular Changes In Wind Wave Heightssupporting
confidence: 76%
“…Carter and Draper (1988) and Bacon andCarter (1991, 1993) from the 16-yr time series recorded at the Seven Stones Light Vessel (SSLV) and Ocean Weather Station (OWS) L reported about 1% yr Ϫ1 secular growth of SWH in the northeast Atlantic from the late 1960s to the early 1980s. Analysis of in situ time series at the National Data Buoy Center (NDBC) buoys in the northeast Pacific (Allan and Komar 2000;Gower 2002) showed upward trends of 12-27 cm decade Ϫ1 in annual mean SWH, with winter (October-March) trends being from 21 to 42 cm decade Ϫ1 during the period of 1978-99. These changes were also confirmed by the long-term estimates of storminess de-rived from the tide gauge residuals (Bromirski et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…They found a trend in mean wave height of 0.23 m decade −1 (1970)(1971)(1972)(1973)(1974)(1975)(1976)(1977)(1978)(1979)(1980)(1981)(1982), whereas Neu (1984) reported larger values between 0.6 and 1.4 m decade −1 . More recent studies of buoy data in the North Pacific have shown increasing trends in average SWH between 0.05 and 0.27 m decade −1 from 1979 to 1999 (Allan and Komar, 2000) and 0.15 m decade −1 for the period 1976-2007 (Ruggiero et al, 2010;Young et al, 2011).…”
Section: Variation In Significant Wave Height From 1979 To 2012mentioning
confidence: 99%
“…Generally significant wave height (SWH) is used to study the wave climate at a location. Globally there have been many studies on the change in wave climate, especially in the North Pacific and North Atlantic regions (Carter and Draper, 1988;Allan and Komar, 2000;Caires and Swail, 2004;Gulev and Grigorieva, 2004;Soomere and Räämet, 2011;Vanem and Walker, 2013). Kumar and Sajiv (2010) carried out a study on variations in long-term wind speed estimates considering different decades in the AS and reported that extreme wind speed has an annual decreasing trend of 1.3 cm s −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Over the 24 year period 1962-1986 the range in average annual significant wave (/2 times root-mean square) height at Seven Stones Light Vessel off Lands End, southwest England, ranged from 2.2 m to 2.9 m with an annual increase of 3 cm/yr. The "50-year return value" ranged from 12 m to 18 m with an increase of 20 cm/yr (Carter and Draper, 1998) 1975-1999(Allen and Komar, 2000. Over this period, the average annual (root-mean square) wave height increased progressively from about 1.6 m to 1.9 m, generating a landward wave energy flux that ranged for these average waves from about 93 x 10 6 kW to 131 x 10 6 kW over the same period.…”
Section: Data Of Instrumented Buoys and Light Vessels In The North Atmentioning
confidence: 99%